(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
In the present study 100 medico legal cases examined for Na+ ion concentration in CSF (cerebrospinal fluid)at different postmortem interval in the department of Forensic Medicine Indira Gandhi Medical College,Nagpur. Analysis revealed that there is decrease in sodium ion concentration with PMI, and shows negativecoefficient correlation r= -0.721. (p<0.001), the least square regression equation is found to be y = -1.027x+ 138.7, where y= sodium ion concentration (independent variable) and x= time since death (dependentvariable). The sodium ion concentration in CSF decreases after death and it is statistically significantbut individual variation is such that we can’t accurately calculate postmortem interval from sodium ionconcentration.